REVISITING TINNITUS AUDIOLOGICAL REHABILITATION - Barros, Anna Carolina Marques Perrella de (2024)
Current research shows tinnitus as more than an auditory phenomenon, but an emotional and cognitive dimension experience. Besides issues involving tinnitus perception and reaction, there is a third dimension: cognition. Both audiological assessment and rehabilitation need to follow these principles and be more comprehensive. The use of sounds to treat tinnitus is described in several papers and has different purposes. It includes hearing aid fitting if hearing loss is detected and the use of sound generator devices. But there are some cases in that hearing loss rehabilitation is not enough and cases of tinnitus and/or sound intolerance suffering without detectable hearing loss in conventional measures. There is no exclusive way for tinnitus patients’ auditory rehabilitation. Based on theoretical proposals and literature, we suggest possibilities of intervention to be even more explored and personally adapted for tinnitus patients: cognitive auditory training and the use of mindfulness-based exercises, sound stimulation during sleep, and restoring the pleasure of listening.